2022
DOI: 10.1101/2022.11.09.22282144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Profiles of children born with Orofacial Clefts: Results from Fourteen East African Countries

Abstract: Background More than 100,000 cleft lip and palate patients have benefited from reconstructive surgeries in Africa as a result of surgical missions by non-governmental organisations such as Smile Train. The Smile Train Express is the largest cleft-centered patient registry with over a million records of clinical records, globally. In this study, we reviewed the east African patient registry data to evaluate and understand the clinical profiles of cleft lip and palate patients operated at Smile Train partner hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…This study is a cross-sectional study utilizing secondary data from the archive of Smile Train Express, a billing software for surgical treatments. Previous studies within the 5 years time-frame have explored the STX database to gain insight of OFC in multiple LMIC settings, 13,[23][24][25][26] or single LMIC settings such as Nigeria. 6 These studies have demonstrated the significant role of a humanitarian organization in enhancing access to care for those in need while also increasing research volume for treatment outcome and epidemiology fields.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
“…This study is a cross-sectional study utilizing secondary data from the archive of Smile Train Express, a billing software for surgical treatments. Previous studies within the 5 years time-frame have explored the STX database to gain insight of OFC in multiple LMIC settings, 13,[23][24][25][26] or single LMIC settings such as Nigeria. 6 These studies have demonstrated the significant role of a humanitarian organization in enhancing access to care for those in need while also increasing research volume for treatment outcome and epidemiology fields.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%